Exploring the causality of appendectomy and ischaemic heart disease: a Mendelian randomization study and meta-analysis - Wang, Shuai; Zhang, Tao; Sun, Yuanlin; Yao, Yiwei; Yang, Dongliang; Cao, Xueyuan (Frontiers in Cardiovascular Medicine, 2024)
Background The risk of ischaemic heart disease (IHD) is increased in appendectomy patients, but it is not clear whether there is a causal relationship. We aimed to systematically estimate the causal relationship between appendectomy and IHD and its subtypes, acute myocardial infarction (AMI) and angina pectoris (AP), using Mendelian randomization (MR) study methods and meta-analysis. Methods As the discovery cohort analysis, we extracted independent genetic variants strongly associated with appendectomy from the FinnGen study (28,601 cases) as instrumental variables (IVs). Genome-wide association study (GWAS) from UK Biobank were selected for outcome data. A first two-sample MR analysis was then conducted. As the replication cohort, IVs associated with appendectomy were extracted in the UK Biobank (50,105 cases). GWAS from the FinnGen study were selected for outcome data. A second MR analysis was then performed. Finally, meta-analyses were applied to assess the combined causal effects of the MR results. Results In the discovery cohort, there was a significant positive causal relationship between appendectomy and IHD and its subtypes AMI and AP. The replication cohort only found a positive causal relationship between appendectomy and AMI. Meta-analysis showed a positive causal relationship between appendectomy and IHD (OR: 1.128, 95% CI: 1.067–1.193, P = 2.459e-05), AMI (OR: 1.195, 95% CI: 1.095–1.305, P = 6.898e-05), and AP (OR: 1.087, 95% CI: 1.016–1.164, P = 1.598e-02). Conclusions This comprehensive MR analysis suggests that genetically predicted appendectomy may be a risk factor for the development of IHD and its subtypes AMI and AP. We need to continue to pay attention to these links.